1999
DOI: 10.1111/j.1095-8649.1999.tb02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors on survival, growth, and production of American shad larvae

Abstract: Episodic increases in temperature of d5 C above 20 C, over 48 h or declines in pH of 1·0 unit from pH 7·0 reduced survival of yolk-sac and feeding-stage larvae of American shad Alosa sapidissima. Over 16 days all measures of survival, growth, and production were more favourable at each higher temperature in the 15-25 C range. More favourable responses were also obtained at the higher prey level (500 v. 50 Artemia nauplii l 1 ) and at the higher pH (7·5 v. 6·5). Combinations of high temperature and high prey le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In line with Leach and Houde (1999), our results suggest that careful choice of the release site is crucial in order to reduce losses. The results indicate that fish should be released in areas without waves, e.g.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with Leach and Houde (1999), our results suggest that careful choice of the release site is crucial in order to reduce losses. The results indicate that fish should be released in areas without waves, e.g.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the weather conditions should be considered if the stocking time table is flexible enough. Also Leach and Houde (1999) point out that timing of the stocking can be critical for return rate of American shad. They advise to avoid too early stocking, when water temperatures are still low, as growth and survival of American shad increases with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…, 2007). In contrast, for organisms that operate below the optimum, warming impacts would occur on the rising curve, possibly providing a functional benefit (Leach and Houde, 1999; Whitledge and Rabeni, 2002; Billman et al. , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…An increased metabolic rate incurred at higher temperatures is also a likely cause of the interaction effect between temperature and food on otolith growth in the present study, where the highest growth was observed in the high temperature/high food treatment. Leach & Houde (1999) also found that a combination of high temperature and high prey levels led to the highest growth rates. A higher metabolic rate may also explain why no larvae from the starved/high temperature treatment survived the full length of the trial, when compared with the starved/low temperature treatment which had a >50% survival.…”
Section: Discussionmentioning
confidence: 88%